Evaluation Formula and Approximation for Wiener Integrals via the Fourier-Type Functional. (4th June 2021) - Chung, Hyun Soo; Lee, Un Gi
Abstract: In order to calculate the Wiener integrals for functionals on Wiener space, one can usually apply the change of variable theorem. But, there are many functionals that are difficult or impossible to calculate even when using the change of variable formula. In order to solve this problem, we establish an evaluation formula via the Fourier-type functionals on Wiener space. We then present various examples to which our evaluation formula can be applied and with the corresponding numerical approximations.